Clinical Evaluation of Forceps Eruption: Reestablishing Biologic Width and Restoring No Restorable Teeth - Khayat, Akbar; Fatehi, Shayan (Iranian Endodontic Journal, 2010)
INTRODUCTION: Complicated crown- root fractures, extended caries and iatrogenic destruction often result in insufficient sound tooth structures and compromise the biologic width. Two common options for re-establishing flap with osseous surgery. Although some advantages are related to these two options, but coronal movement of gingival and alveolar bone in orthodontic extrusion, esthetic problem and inconsistent topography between the involved tooth and the adjacent teeth following osseous surgery are the involved tooth and the adjacent teeth following osseous surgery are the major disadvantages of these two approaches. The purpose of this investigation was to evaluate clinically as well as radiographically the effect of surgical extrusion upon the surrounding root structures. MATERIALS AND METHODS: The material consisted of 21 developed single roots (1 upper and 3 lower) surgically extruded in 17 patients (15 male and 2 female mean age 26 years, ranging 10-40). The indication for surgical extrusion was in 15 cases complicated crown root fracture and in 6 cases early loss of the crown due to an extensive decay. The roots were used where there were completed root developments and the apical fragments were long enough to accommodate a post retained crown. Preoperative radiograph as well as photograph was taken and the clinical and radiographic findings were monitored. The roots were transplanted in their socket in order to reestablish the biologic width. Fixation was carried out with a suture splint and/ or periodontal dressing for 7 days. Recall radiographs were taken at 1 and 4 weeks and at 3 month internals over a 12- month period. RESULTS: Clinically none of the material of 21 teeth demonstrated ankylosis, abnormal mobility and sensibility to percussion or palpation radiographically, PDL healing at 12- month follow up was found in 20 teeth (95.2%). CONCLUSION: successful results up to the time of evaluation encouraged further use of surgical extrusion. Long term evaluation is recommended.